Construction of Marketplace Responsibility In Consumer Protection of Digital Halal Products In Indonesia - Ananda Gymnastiar Dwijaya; Harmono Harmono (Ann Publisher, 2025)
Aims. This study analyzes the construction of marketplace liability in protecting consumers of halal products in Indonesia's digital economy. Methods. The research employs a normative legal method with statutory, conceptual, comparative, and case approaches. Data were obtained from primary legal materials such as laws, government regulations, and ministerial regulations, as well as secondary sources, including academic journals and reports from halal certification authorities. Result. The findings reveal that marketplaces cannot be considered neutral intermediaries, but rather business actors under the Consumer Protection Law, with obligations to ensure the accuracy and truthfulness of halal claims. The absence of explicit technical regulations on halal verification in electronic commerce has created a legal vacuum that weakens consumer protection. Comparative analysis of Malaysia, the United Arab Emirates, and the European Union shows that due diligence obligations for platforms have proven effective in minimizing false halal claims. Conclusion. This study concludes that Indonesia requires conditional safe harbor mechanisms, layered accountability, and mandatory integration with BPJPH's halal database to strengthen legal certainty and consumer trust in the halal digital ecosystem.